Overview of the commemorations of the Bicentenary of the French Invasions - Monteiro, Isilda (2016)
The commemorations of the French invasions in Portugal continued until the end of September 2010, this being the date that marked two hundred years since the Battle of Buçaco. These commemorations did not yet mark the date of the definitive withdrawal of the invading forces from Portuguese territory, which was only to happen in early April 1811, when, under the command of Massena, the French troops, already having been defeated and confronted with the defensive complex formed by the lines of Torres Vedras that barred their advance upon Lisbon, crossed over the border from Portugal to Spain, bringing an end to what was to become known as the 3rd French Invasion.3 The date of the Battle of Buçaco is, however, of important symbolic significance as it represented the moment when the Anglo-Portuguese army, under the command of General George Wellington, defeated the French army, thereby marking a decisive turning point in the confrontations with the invading forces, a moment that, at that time, was immediately and enthusiastically signaled by the remarkable musical composition of António José do Rego (c. 1765-post 1844) in his work entitled A Batalha do Buçaco. As David Cranmer recently demonstrated, this musical piece, composed in 1810, offers a highly detailed description of its context, relating the first events in the confrontation and closely accompanying the text of the official notice by Lord Wellington, published a week later in the Gazeta de Lisboa, 3 October 1810 (CRANMER, 2007: II, 239-51).